The Politics of Right Sex : Transgressive Bodies, Governmentality, and the Limits of Trans Rights - Daum, Courtenay W. (Book collections on Project MUSE., 2020)
"While the growing attention to trans rights and the development of trans specific interest groups suggest that the time is right for a trans rights movement akin to prior civil rights movements, The Politics of Right Sex explores the limitations of rights-based mobilization and litigation for advancing the interests of trans communities. Synthesizing critical theory, transgender studies, and extant law and society research, author Courtenay W. Daum argues that trans individuals, particularly those situated at the intersection of gender, race, class, and immigration status, are regulated by myriad forces of governmentality that work to maintain the sex and gender binaries and associated power hierarchies. Because many informal practices and norms are located beyond the reach of civil rights laws, a trans politics of rights may produce some modest legal and legislative reforms but will not eliminate the disciplinary forces that work to subject trans individuals and will privilege those transgender individuals who are able to conform with dominant gender norms at the expense of the interests of gender non-conforming, gender queer, trans people of color, and others unable or unwilling to embrace a transnormative presentation of self and/or lifestyle. As such, The Politics of Right Sex advocates for a more confrontational approach that directly engages and challenges the hegemonic power structures that govern and discipline trans individuals, to disrupt the dominant discourse and hierarchical power arrangements in pursuit of collective liberation for all as opposed to rights for some"--